Effect of genotype on individual response to the pharmacological treatment of glaucoma: a systematic review and meta-analysis - Damiana Scuteri; Giulio Pocobelli; Yoichi Sakurada; Rossella Russo; Paolo Tonin; Pierluigi Nicotera; Giacinto Bagetta; Maria Tiziana Corasaniti; Carlo Nucci (Biology Direct, 2023)
Abstract The social impact of glaucoma is worth of note: primary open-angle glaucoma (POAG) is one of the leading causes of irreversible blindness worldwide, affecting some 68.56 million people with overall prevalence of 2.4%. Since one of the main risk factors for the development of POAG is the increase of intraocular pressure (IOP) causing retinal ganglion cells death, the medical treatment of POAG consists in the use of drugs endowed with neuroprotective effect and able to reduce IOP. These drugs include beta-blockers, prostaglandin analogues, carbonic anhydrase inhibitors, alpha or cholinergic agonists and rho kinase inhibitors. However, not all the patients respond to the same extent to the therapy in terms of efficacy and safety. Genetics and genome wide association studies have highlighted the occurrence of mutations and polymorphisms influencing the predisposition to develop POAG and its phenotype, as well as affecting the response to pharmacological treatment. The present systematic review and meta-analysis aims at identifying genetic variants and at verifying whether these can influence the responsiveness of patients to therapy for efficacy and safety. It follows the most updated Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 recommendations. The literature search was conducted consulting the most relevant scientific databases, i.e. PubMed/MEDLINE, Scopus, Web of Science and Public Health Genomics and Precision Health Knowledge Base up to June 14th, 2023. The search retrieved 1026 total records, among which eight met the eligibility criteria for inclusion in the analysis. The results demonstrated that the most investigated pharmacogenetic associations concern latanoprost and timolol, and that efficacy was studied more in depth than safety. Moreover, the heterogeneity of design and paucity of studies prompt further investigation in randomized clinical trials. In fact, adequately powered and designed pharmacogenetic association studies are needed to provide body of evidence with good certainty for a more appropriate use of medical therapy in POAG. PROSPERO registration: CRD42023434867.